Нові матеріали до біографії Данила Щербаківського - Білокінь, С. (Студії мистецтвознавчі, 2009)
The scale of the work that has been done, the work with the original sources which haven’t been pulled out from their environment and their society yet, and the elements of exclusiveness related to the academics’ study of artefacts that later perished in different circumstances, recordings of such artefacts define the hierarchy of values in the heritance of Ukrainian art historians. The greatest input for the Humanities in this sphere was made by Danylo Shcherbakivskyi (1877–1927), Kost Shyrotskyi (1886–1919), Stefan Taranushenko (1899–1976), et al. Their lives and deaths, certain unimplemented plans, and loss of part of the archives make us pay exceptional attention to source studying issues and to the presence of the extant materials in archives, in particular. This publication introduces Shcherbakivskyi’s letters to his father, his sister’s memoirs that reveal some circumstances that were not covered in literature, Posternak’s letter to his sister, etc.